ENVIRONMENTAL GRAPHIC DESIGN OF MPU TANTULAR MUSEUM - Masnuna Masnuna (Universitas Sebelas Maret, 2019)
The museum is the storage and preservation of cultural heritage and historic objects for the benefit of the study, research, or entertainment. A museum should be able to provide accurate information and adequate facilities. In order for the historical objects and museum facilities to be optimally enjoyed by visitors, the museum requires environmental graphics to assist the course of the visit. Mpu Tantular Museum which is located in Sidoarjo does not yet have sufficient signposts and information boards, causing the visitors to be confused. Then there is the need for environmental graphics to assist the visitors in finding and getting the maximum information. This paper will design the environmental graphics of Mpu Tantular Museum with a design concept called